The Correct Strategy for Creating a Speech Manuscript in Identifying a Quality Manuscript - Sitti Aisyah; Faridatul Jannah; Desi Endang Maisuri; Fitri Inayah (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2025)
Creating a quality manuscript is an important foundation in various disciplines, both academic and non-academic. This process requires not only writing skills, but also a deep understanding of the structure, style, and purpose of writing. This article discusses the right strategy in compiling a manuscript by paying attention to quality elements, as well as how to identify the characteristics of a good manuscript. Through a qualitative-descriptive approach, the author describes the steps that can be applied by novice and professional writers in producing effective and high-quality manuscripts.